STRATEGI WAHANA LINGKUNGAN HIDUP INDONESIA (WLHI) DALAM MENJAGA STABILITAS POLITIK LOKAL: STUDI KASUS KONFLIK PERTAMBANGAN DI KALIMANTAN - Auerella Shalsabilla Agatha (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The expansion of the extractive industry in Kalimantan not only triggers ecological degradation but also creates political volatility that threatens regional stability. This study explores the strategies of Wahana Lingkungan Hidup Indonesia (WLHI) in navigating agrarian conflicts to prevent social disintegration. Using a framework of Political Ecology and Transformative Conflict Management, this qualitative study examines how WLHI transforms mass resistance into a structured, formal-legal movement. The findings indicate that WLHI’s strategies including strategic litigation, counter-mapping, and the strengthening of civic politics serve as a “safety valve” for local democracy. In conclusion, political stability in mining conflict zones is not achieved through repression, but rather through the inclusion of ecological justice agendas within the state’s legal system